(NsOWREMENNYJ RUSSKIJ LITERATURNYJ QZYK (B:s (Nu^EBNOE POSOBIE (B/s - (NgOLXCOWA(B, (Nn(B.(Ng(B.s; (NvUKOW(B, (Nw(B.(Np(B.s; (NkASATKIN(B, (NlEONID lEONIDOWI^s; (NlEKANT(B, (NpAWEL aLEKSANDROWI^s ((NmOSKWA (B:s (NwYS[(B. (N[K(B.,s, 1988)
(NbIBLIOGR(B.: (NS(B. 410-411s
Keywords: (NrUSSKIJ LITERATURNYJ QZYKs